Factors affecting the value of the insurance policy An exploratory study on Saudi health insurance companies - Al-shahrani, Ashwaq Safar (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of the research was to identify the factors influencing the decisions of determining the value of the insurance policy. The research used the analytical descriptive method. The questionnaire was used as a tool for gathering information from the study members. The comprehensive survey method was applied by applying all insurance companies in the Kingdom of Saudi Arabia. The sample of the study was 200 employees, and the research reveals several results, the most important of which is that the insurance policy is different according to the type of contract which affects its value Relative weight 0.83. The size of danger determines the type, value and period of the insurance policy Relative weight 82.20. This affects the value of the insurance policy, with higher the health service provided to the insured. The study recommends the need to pay attention to health insurance and the need to raise the awareness among citizens about importance of health insurance. Also, insurance companies should minimize the limit of installment and it should include a large part of health services costs. In addition, they need to clarify more about the covering limit by the premium insurance policy, which may help to reduce the price of the insurance policy to suit all members of society in order to obtain the appropriate health services for them.